Preparation method of multiphase silicon carbide ceramic and multiphase silicon carbide ceramic
Through the preparation method of composite phase silicon carbide ceramics, the problems of existing silicon carbide ceramics are solved, and complex phase silicon carbide ceramics with high thermal conductivity and strong impact toughness are prepared. Improves the high-frequency performance and long-term reliability of piston compressors.
Patent Information
- Application Number
- CN202411294378.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-20
AI Technical Summary
The existing silicon carbide ceramic materials are hard and brittle in piston compressors, difficult to process, easy to collapse, poor friction coefficient, and inappropriate thermal expansion coefficient, resulting in the compressor's high-frequency performance, increased noise, and low thermal conductivity. Inability to conduct heat effectively.
Using the preparation method of compound-phase silicon carbide ceramics, silicon carbide, aluminum, hexagonal boron nitride, silicon nitride and sintering additives as raw materials, it is prepared by mixing, stirring, pressing, heating and tri-stage sintering treatment of ball mills. Complex phase silicon carbide ceramics with high thermal conductivity, impact toughness, self-lubricity and suitable thermal expansion coefficient.
It improves the density, wear resistance and thermal conductivity of composite phase silicon carbide ceramics, reduces processing costs, enhances the high-frequency performance and long-term reliability of piston compressors, reduces noise and vibration, and improves friction performance.
Smart Images

Figure CN119161188A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of silicon carbide ceramic materials, and in particular to a preparation method of a multiphase silicon carbide ceramic and the multiphase silicon carbide ceramic. Background Art
[0002] When the piston compressor compresses the refrigerant gas, the temperature of the refrigerant gas rises, which in turn causes the cylinder, piston, connecting rod and other components to be heated and the temperature to rise. The refrigerant gas inhaled in the next compression cycle will be heated and expanded, which will cause the amount of refrigerant gas inhaled to decrease. Therefore, the materials used for components such as the cylinder, piston, piston pin, and connecting rod should have good thermal conductivity to ensure that the heat can be carried away by the lubricating oil flowing through these components in time.
[0003] The thermal conductivity of alumina ceramics in related technologies is 1 / 2 times that of cast iron, the thermal conductivity of zirconia ceramics is 1 / 20 times that of cast iron, and the thermal conductivity of silicon carbide is 3 times that of cast iron. That is, the thermal conductivity of zirconia and alumina ceramics is relatively low and their practicality is poor; and silicon carbide ceramics with high thermal conductivity among ceramic materials have become the most ideal base material for components such as pistons, piston pins, and connecting rods.
[0004] However, the silicon carbide ceramic material in the related art is hard and brittle, and its hardness is second only to diamond. It is not easy to grind and is difficult to process. It will be at risk of breaking and fragmentation when subjected to a large impact or grinding. In addition, since the silicon carbide ceramic material in the related art does not contain a graphite lubricating phase similar to cast iron materials, the friction coefficient is poor. At the same time, the thermal expansion coefficient of the silicon carbide ceramic material in the related art is (4.0-4.8)×10 -6 / ℃, if it is used as the base material of the piston, and the silicon carbide ceramic piston is connected with a thermal expansion coefficient of (8.0~10.0)×10 -6 / ℃ cast iron material is used for matching. When the compressor is running under high-frequency conditions, the cylinder and piston will be easily deformed as the temperature rises, which will cause the matching clearance between the cylinder and the piston to gradually increase, aggravate the power loss, and thus greatly reduce the high-frequency performance of the compressor. Summary of the invention
[0005] In view of the above problems, a method for preparing a multiphase silicon carbide ceramic and a multiphase silicon carbide ceramic are proposed to overcome the above problems or at least partially solve the above problems, including:
[0006] A method for preparing a multiphase silicon carbide ceramic, the method comprising:
[0007] Silicon carbide, aluminum, hexagonal boron nitride, silicon nitride and a sintering aid are used as first raw materials, and the first raw materials are subjected to ball milling and mixing treatment in deionized water to obtain a uniformly mixed prefabricated mixture;
[0008] The prefabricated mixed material, the adhesive, the surfactant and the lubricant are used as the second raw material, and the second raw material is stirred and mixed to obtain a uniformly mixed prefabricated material;
[0009] The prefabricated material is subjected to a compression molding process to obtain a prefabricated green material;
[0010] The prefabricated green material is subjected to a heating and debinding treatment to obtain a green billet;
[0011] Sintering the green body to obtain a composite silicon carbide ceramic blank;
[0012] The composite silicon carbide ceramic blank is machined to obtain the composite silicon carbide ceramic.
[0013] Optionally, the silicon carbide accounts for 46% to 84% of the total mass of the first raw material, the aluminum accounts for 10% to 15% of the total mass of the first raw material, the hexagonal boron nitride accounts for 2% to 28% of the total mass of the first raw material, the silicon nitride accounts for 2% to 5% of the total mass of the first raw material, the sintering aid accounts for 2% to 6% of the total mass of the first raw material, and the processing time of the ball milling mixing treatment is 3h to 5h.
[0014] Optionally, the prefabricated mixture accounts for 81% to 94% of the total mass of the second raw material, the adhesive accounts for 5% to 15% of the total mass of the second raw material, the surfactant accounts for 1% to 3% of the total mass of the second raw material, and the lubricant accounts for 0% to 1% of the total mass of the second raw material.
[0015] Optionally, the molding pressure of the compression molding process is 60MPa to 120MPa, and the holding time is 5min to 10min; the compression molding process of the prefabricated material includes:
[0016] The prefabricated material is subjected to compression molding and / or cold isostatic pressing to obtain the prefabricated green material.
[0017] Optionally, the temperature of the heating debinding treatment is 200° C. to 400° C., and the insulation time is 0.5 h to 3.0 h.
[0018] Optionally, the sintering the green compact includes:
[0019] The green body is subjected to vacuum sintering treatment, atmosphere normal pressure sintering treatment and atmosphere hot pressing sintering treatment in sequence to obtain the composite silicon carbide ceramic blank.
[0020] Optionally, the green body is subjected to vacuum sintering, atmospheric pressure sintering and atmosphere hot pressing sintering in sequence, including:
[0021] Acquiring sintering temperature information in a sintering environment, and controlling the sintering gas pressure in the sintering environment to be less than 100 Pa before the sintering temperature rises to 1600° C. to 1800° C., so as to perform the vacuum sintering treatment on the green body;
[0022] When the sintering temperature rises to 1600° C. to 1800° C., 0.1 MPa of nitrogen is introduced into the sintering environment, and then the sintering temperature is controlled to rise to 2000° C. to 2300° C. and kept at this temperature for 0.5 h to 1.5 h, so as to perform the atmosphere normal pressure sintering treatment on the green body;
[0023] After the atmospheric pressure sintering treatment is completed, the nitrogen gas is continuously introduced into the sintering environment, and the sintering gas pressure is increased to 0.5 MPa to 1.0 MPa, and then the temperature is maintained for 1 h to 2 h to perform the atmospheric hot pressing sintering treatment on the green body.
[0024] Optionally, the melting point of the sintering aid is higher than 2300° C., and the sintering aid is one or more of boron carbide, yttrium trioxide and beryllium oxide.
[0025] Optionally, the silicon carbide is a mixed silicon carbide powder comprising three particle size grades, wherein the first particle size grade silicon carbide powder: the second particle size grade silicon carbide powder: the third particle size grade silicon carbide powder = 8:6:5;
[0026] The first particle size grade silicon carbide powder accounts for 46% to 54% of the total mass of the mixed silicon carbide powder, the second particle size grade silicon carbide powder accounts for 16% to 20% of the total mass of the mixed silicon carbide powder, and the third particle size grade silicon carbide powder accounts for 26% to 38% of the total mass of the mixed silicon carbide powder;
[0027] The particle size of the silicon carbide powder of the first particle size grade is 20 μm to 30 μm, the particle size of the silicon carbide powder of the second particle size grade is 7 μm to 20 μm, and the particle size of the silicon carbide powder of the third particle size grade is 5 μm to 15 μm.
[0028] Optionally, during the ball milling mixing process, the first raw material: grinding ball: deionized water = 1.0: (1.2-1.5): (1.0-1.2); the grinding ball is a silicon carbide grinding ball.
[0029] Optionally, the adhesive is a polyvinyl alcohol solution, the surfactant is one or more of polyacrylate, hydroxymethyl cellulose, sodium hydroxymethyl cellulose and lignin sulfonate, and the lubricant is one or more of oleic acid, zinc stearate, magnesium stearate and paraffin.
[0030] A multiphase silicon carbide ceramic is prepared by the method for preparing the multiphase silicon carbide ceramic as described above.
[0031] A compressor comprises the multiphase silicon carbide ceramic as described above.
[0032] The embodiments of the present invention have the following advantages:
[0033] The invention provides a preparation method of a composite silicon carbide ceramic. Silicon carbide, aluminum, hexagonal boron nitride, silicon nitride and a sintering aid are used as first raw materials, and the first raw materials are subjected to ball milling and mixing treatment in deionized water to obtain a uniformly mixed prefabricated mixture; then the prefabricated mixture, an adhesive, a surfactant and a lubricant are used as second raw materials, and the second raw materials are stirred and mixed to obtain a uniformly mixed prefabricated material; then the prefabricated material is pressed and molded to obtain a prefabricated green blank; then the prefabricated green blank is heated and subjected to binder removal treatment to obtain a green blank; thus, the green blank is sintered to obtain a composite silicon carbide ceramic blank; and then the composite silicon carbide ceramic blank is machined to obtain the composite silicon carbide ceramic. The multiphase silicon carbide ceramic prepared by the method provided by the present invention has the advantages of low density, high wear resistance, high thermal conductivity, strong impact toughness, strong friction reduction and self-lubricating property, and a higher thermal expansion coefficient than the existing silicon carbide ceramics. The multiphase silicon carbide ceramic is easier to process and can reduce the loss of PCD (Polycrystalline diamond) tools and diamond grinding wheels, thereby reducing the processing cost. At the same time, after the multiphase silicon carbide ceramic material is used as the base material of the piston, piston pin, connecting rod and other parts of the piston compressor, it will have a significant positive effect on improving the performance of the compressor, reducing vibration and reducing noise. Its ultra-high wear resistance also provides a stronger guarantee for the long-term operation reliability of the compressor. Even if the compressor is operated under high-frequency conditions for a long time, it will not fail due to wear. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solution of the present invention, the accompanying drawings required for use in the description of the present invention will be briefly introduced below. Obviously, the accompanying drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative labor.
[0035] Figure 1 is a flow chart of steps of a method for preparing a multiphase silicon carbide ceramic provided by some embodiments of the present invention;
[0036] Figure 2 is an overall flow chart of a method for preparing a multiphase silicon carbide ceramic provided in some embodiments of the present invention;
[0037] Figure 3 is a cross-sectional view of a piston compressor provided by some embodiments of the present invention;
[0038] Figure 4 is a three-dimensional diagram of a piston compressor core assembly provided by some embodiments of the present invention;
[0039] Figure 5 is a three-dimensional diagram of a piston compressor pump assembly provided by some embodiments of the present invention;
[0040] Figure 6 It is a three-dimensional diagram of the piston assembly, crankshaft assembly and connecting rod assembly provided by some embodiments of the present invention;
[0041] Figure 7 is a three-dimensional diagram of a crankshaft provided by some embodiments of the present invention;
[0042] Figure 8 are three-dimensional diagrams and cross-sectional diagrams of connecting rods provided in some embodiments of the present invention;
[0043] Fig. 9 is a three-dimensional diagram of a piston provided by some embodiments of the present invention;
[0044] Fig.10 is a three-dimensional diagram of a piston pin provided by some embodiments of the present invention;
[0045] Fig.11 It is a distribution diagram of the lateral force and the residual reciprocating inertial force generated by the piston during the operation of the compressor of the conventional solution and the solution of the present invention provided by some embodiments of the present invention;
[0046] Fig.12 This is a comparison diagram of compressor noise of the conventional solution provided by some embodiments of the present invention and the multi-phase SiC ceramic component solution of the present invention;
[0047] Fig.13 This is a comparison chart of the compressor refrigeration capacity of the conventional solution provided by some embodiments of the present invention and the multi-phase SiC ceramic component solution of the present invention;
[0048] Fig.14 It is a comparison chart of friction coefficients of conventional metal material solutions provided by some embodiments of the present invention and the multiphase SiC ceramic material solution of the present invention;
[0049] Fig.15 This is a comparison chart of compressor power consumption of the conventional solution provided in some embodiments of the present invention and the complex SiC ceramic component solution of the present invention.
[0050] Explanation of reference numerals: 101-step 1 of the method for preparing the multiphase silicon carbide ceramic of the present invention; 102-step 2 of the method for preparing the multiphase silicon carbide ceramic of the present invention; 103-step 3 of the method for preparing the multiphase silicon carbide ceramic of the present invention; 104-step 4 of the method for preparing the multiphase silicon carbide ceramic of the present invention; 105-step 5 of the method for preparing the multiphase silicon carbide ceramic of the present invention; 106-step 6 of the method for preparing the multiphase silicon carbide ceramic of the present invention; 100-housing assembly; 200-movement assembly; 210-cylinder seat; 220-motor assembly; 230-crankshaft assembly; 240-connecting rod; 250- Piston assembly; 260-valve assembly; 270-muffler assembly; 280-end cover; 231-crankshaft; 232-counterweight; 251-piston; 252-piston pin; 253-circlip; 231a-main oil channel; 231b-first branch oil channel; 231c-second branch oil channel; 231d-first spiral oil channel; 231e-third branch oil channel; 231f-second spiral oil channel; 241-rod; 242-main shaft hole; 243-secondary shaft hole; 243-straight oil channel; 251a-boss; 251b-pin hole; 251c-circlip hole; 252a-pin retaining ring hole. DETAILED DESCRIPTION
[0051] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0052] In the embodiments of the present application, words such as "first" and "second" are used to distinguish between identical or similar items with basically the same functions and effects. This is only for the purpose of clearly describing the technical solutions of the embodiments of the present application, and shall not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features.
[0053] In the embodiments of the present application, the terms "upper", "lower", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.
[0054] Refrigerators can provide long-term preservation for vegetables, fruits, meat and eggs and other foods, and are essential household appliances in daily life. As people's demand for the fresh taste of food gradually increases, higher requirements are also put forward for food preservation technology, especially for fresh meat food. Refrigerators need to be able to quickly refrigerate and achieve the effect of instant freezing, that is, refrigerators need to be able to quickly refrigerate and reach below -30℃. This requires that the operating frequency of the piston compressor for refrigerators can be quickly increased to a high frequency of more than 100Hz, and can operate stably for a long time under this high-frequency working condition. After the temperature in the refrigerator stabilizes, the compressor automatically operates at a low frequency of less than 30Hz; that is, as the demand for refrigerator preservation ability increases, the operating requirements for compressors also increase, thereby promoting refrigerator piston compressors to gradually develop in the direction of broadband, high speed and high efficiency.
[0055] Generally speaking, when the piston compressor for refrigerators is running, the motor will drive the crankshaft with an eccentric structure so that the connecting rod drives the piston to move linearly in the cylinder, and then perform a cyclic working process of suction, compression and exhaust of the refrigerant gas. During the rotational operation of the crankshaft with an eccentric structure, it is impossible to eliminate the reciprocating inertia force generated by the eccentric structure, and the power loss caused by overcoming the inertia force cannot be avoided; and in the related technology, the piston, piston pin, connecting rod and crankshaft and other moving parts of the piston compressor for refrigerators are all made of iron-based materials with high density. The power loss caused by the unbalanced reciprocating inertia force during the operation of the compressor is large, and the power loss will gradually increase with the increase of the operating frequency of the compressor, and will cause the vibration of the compressor to intensify, the noise to increase, and affect the user experience.
[0056] When the piston compressor for refrigerator compresses the refrigerant gas, the temperature of the refrigerant gas rises, which in turn causes the cylinder, piston, connecting rod and other parts to be heated and the temperature rises. The refrigerant gas inhaled in the next compression cycle will be heated and expand, which in turn causes the amount of refrigerant gas inhaled to decrease. Therefore, it is necessary not only to optimize the oil circuit structure of the compressor's lubricating oil to facilitate the lubricating oil to take away the heat in time, but also the materials used for the cylinder, piston, piston pin, connecting rod and other parts must have good thermal conductivity, so that the heat can be taken away by the lubricating oil flowing through these parts in time. For example, ceramic materials with low density and good wear resistance are used as the base material of the moving parts of the piston compressor for refrigerators, such as zirconium oxide, aluminum oxide, silicon carbide and other ceramic materials, to reduce the adverse effects of unbalanced inertial force, and ultimately achieve the purpose of improving performance, reducing vibration and reducing noise. Among them, the thermal conductivity of alumina ceramics is 1 / 2 times that of cast iron, the thermal conductivity of zirconia ceramics is 1 / 20 times that of cast iron, and the thermal conductivity of silicon carbide is 3 times that of cast iron. Since the thermal conductivity of zirconia and alumina ceramics is relatively low, silicon carbide ceramics with high thermal conductivity among ceramic materials have become the most ideal base material for components such as pistons, piston pins, and connecting rods.
[0057] However, the silicon carbide ceramic material in the related art is hard and brittle, and its hardness is second only to diamond. It is not easy to grind and is difficult to process. It is at risk of breaking and fragmenting when subjected to large impact or grinding. Moreover, since the silicon carbide ceramic material in the related art does not have a graphite lubricating phase similar to cast iron materials, its friction coefficient is worse than that of cast iron. When it is used as a base material for parts with friction pairs in piston compressors for refrigerators, the friction power loss of the compressor increases. At the same time, the thermal expansion coefficient of the silicon carbide ceramic material in the related art is (4.0~4.8)×10 -6 / ℃, if it is used as the base material of the piston, and the silicon carbide ceramic piston is connected with a thermal expansion coefficient of (8.0~10.0)×10 -6 / ℃ cast iron material is used for matching. When the compressor is running under high-frequency conditions, the increase in temperature will cause the cylinder and piston to deform, resulting in the gradual increase in the matching clearance between the cylinder and the piston, aggravating the power loss caused by leakage, and thus greatly reducing the high-frequency performance of the compressor.
[0058] For example, a method for preparing SiC ceramic parts disclosed in the related art includes mixing 90.6-98.6wt% SiC micron powder, 0.5-2wt% adhesive, 0.5-1.5wt% dispersant and 0.4-1.2wt% defoamer in a solvent and spray granulating, wherein 5-15wt% nano carbon black is also added to the SiC powder, and 1-5μm SiC granulated powder is evenly mixed with 10-50μm SiC ordinary powder, and the mixing mass ratio is (1-2):1, and finally 3DP printing is performed in sequence to obtain a green body, cracking reaction to obtain a dense body, and reactive sintering to obtain SiC ceramic parts. However, the 3DP printing technology used is costly and inefficient, and its carbon black is easily oxidized during the sintering process without the protection of an inert atmosphere, which leads to a decrease in the self-lubricating performance of the sintered SiC ceramic parts.
[0059] In order to solve the above problems, the present invention improves the preparation method of multi-phase silicon carbide ceramics in the related art based on the core technical concept of preparing a new type of multi-phase silicon carbide ceramics. The present invention will be described in detail in conjunction with the accompanying drawings below:
[0060] Reference Figure 1 , shows a flow chart of steps of a method for preparing a multiphase silicon carbide ceramic provided by some embodiments of the present invention, which may specifically include the following steps:
[0061] Step 101, using silicon carbide, aluminum, hexagonal boron nitride, silicon nitride and a sintering aid as first raw materials, and subjecting the first raw materials to a ball-milling mixing process in deionized water to obtain a uniformly mixed prefabricated mixture;
[0062] In a specific implementation, 46.0-84.0wt.% SiC, 10.0-15.0wt.% Al, 2.0-28.0wt.% hexagonal BN as a lubricating medium, 2.0-5.0wt.% Si3N4 and 2.0-6.0wt.% sintering aid can be ball-milled and mixed in deionized water with WC ceramic balls (silicon carbide grinding balls) for 3-5h, and the mixed ingredients (i.e., the first raw material) of the ball-milling mixing treatment are: grinding balls: deionized water = 1.0: (1.2-1.5): (1.0-1.2), and after drying, a uniformly mixed prefabricated mixture is obtained for subsequent steps;
[0063] Among them, Al, which is easily soluble in SiC, forms a substitutional solid solution with SiC at high temperature, thereby promoting the sintering of the multiphase silicon carbide ceramic to be denser; and part of Al forms an AlN ceramic phase with a thermal conductivity of 50 to 75 W / (mm°C) when sintered in a nitrogen atmosphere. The AlN is also a sintering aid for SiC ceramics, further making the sintered multiphase silicon carbide ceramic material denser; hexagonal BN has self-lubricating properties, and its lubricating properties are better than other solid lubricants (such as molybdenum disulfide and graphite). It can also maintain good self-lubricating properties at high temperatures. After adding the lubricating medium hexagonal BN, it can not only improve the processing performance of the multiphase silicon carbide ceramic, enhance its material toughness, and is not prone to collapse and fragmentation during processing, but also The invention can enhance the self-lubricating property of the composite silicon carbide ceramics; Si3N4 can form a liquid phase during high temperature sintering and infiltrate into the pores of the prefabricated green body formed by pressing, thereby improving the sintering property and increasing the density of the composite silicon carbide ceramics; after adding one or more sintering aids of boron carbide, yttrium trioxide and beryllium oxide, the dispersion of SiC ceramic phase, AlN ceramic phase, BN ceramic phase and Si3N4 ceramic phase in the composite silicon carbide ceramics can be further reduced, that is, these ceramic phases are distributed more evenly, thereby increasing the strength of the green body and thus improving the density of the green body. Since the sintering molding temperature of SiC is 2000℃~2300℃, in order to prevent these sintering aids from melting and decomposing at high temperature, thereby causing AlN, Si3N4 and Al to be decomposed, O 2- Therefore, the melting point of the sintering aid needs to be controlled above 2300°C.
[0064] Furthermore, due to the addition of Al (22.5-22.3×10 -6 / ℃), and partially reacts with nitrogen at high temperature to form AlN with a relatively high linear expansion coefficient (5.0~6.0×10 -6 / ℃), so that the thermal expansion coefficient of the composite silicon carbide ceramic can reach (6.0~7.3)×10 -6 / ℃, that is, its thermal expansion coefficient is higher than that of existing silicon carbide ceramic materials.
[0065] In addition, since the thermal conductivity of the raw materials SiC (120W / (mmK)), Al (100W / (mmK)), AlN (70W / (mmK)), and BN (50W / (mmK)) are higher than that of the existing iron-based materials (50W / (mmK)), the thermal conductivity of the high-density multi-phase silicon carbide ceramic can reach more than 80W / (mmK), that is, the thermal conductivity of the multi-phase silicon carbide ceramic material of the present invention is at least 2 times higher than that of the existing iron-based materials.
[0066] The above Al, AlN formed by the reaction, hexagonal BN, Si3N4 and sintering aids play a synergistic improvement role on the multiphase silicon carbide ceramics, so that the multiphase silicon carbide ceramic material after sintering has high density, good impact toughness, high hardness, strong wear resistance, high thermal conductivity, good friction reduction and self-lubrication, and a higher thermal expansion coefficient than the existing silicon carbide ceramics. It is easy to process and reduces the wear of PCD tools and diamond grinding wheels.
[0067] In some embodiments of the present invention, the silicon carbide accounts for 46% to 84% of the total mass of the first raw material, the aluminum accounts for 10% to 15% of the total mass of the first raw material, the hexagonal boron nitride accounts for 2% to 28% of the total mass of the first raw material, the silicon nitride accounts for 2% to 5% of the total mass of the first raw material, the sintering aid accounts for 2% to 6% of the total mass of the first raw material, and the processing time of the ball milling mixing treatment is 3h to 5h.
[0068] In practical applications, 46.0-84.0wt.% SiC, 10.0-15.0wt.% Al, 2.0-28.0wt.% hexagonal BN as a lubricating medium, 2.0-5.0wt.% Si3N4 and 2.0-6.0wt.% sintering aid can be milled and mixed in deionized water with WC ceramic balls (silicon carbide grinding balls) for 3-5 hours to obtain a prefabricated mixture.
[0069] In some embodiments of the present invention, the melting point of the sintering aid is higher than 2300° C., and the sintering aid is one or more of boron carbide, yttrium trioxide and beryllium oxide.
[0070] In practical applications, after adding one or more sintering aids such as boron carbide, yttrium trioxide and beryllium oxide, the dispersion of SiC ceramic phase, AlN ceramic phase, BN ceramic phase and Si3N4 ceramic phase in the multiphase silicon carbide ceramic can be further reduced, that is, these ceramic phases are distributed more evenly, thereby improving the strength of the green body and further improving the density of the green body. Since the sintering molding temperature of SiC is 2000℃~2300℃, in order to prevent these sintering aids from melting and decomposing at high temperature, thereby causing AlN, Si3N4 and Al to be decomposed, O 2-Therefore, the melting point of the sintering aid needs to be controlled above 2300°C.
[0071] In some embodiments of the present invention, the silicon carbide is a mixed silicon carbide powder comprising three particle size grades, wherein the first particle size grade silicon carbide powder: the second particle size grade silicon carbide powder: the third particle size grade silicon carbide powder = 8:6:5;
[0072] The first particle size grade silicon carbide powder accounts for 46% to 54% of the total mass of the mixed silicon carbide powder, the second particle size grade silicon carbide powder accounts for 16% to 20% of the total mass of the mixed silicon carbide powder, and the third particle size grade silicon carbide powder accounts for 26% to 38% of the total mass of the mixed silicon carbide powder;
[0073] The particle size of the silicon carbide powder of the first particle size grade is 20 μm to 30 μm, the particle size of the silicon carbide powder of the second particle size grade is 7 μm to 20 μm, and the particle size of the silicon carbide powder of the third particle size grade is 5 μm to 15 μm.
[0074] In practical applications, in order to improve the packing density and reduce the porosity of the prefabricated green blanks and the sintered composite silicon carbide ceramic blanks formed by subsequent pressing, the SiC powder can be divided into three mixed SiC powders of three particle sizes, and the first particle size grade silicon carbide powder: the second particle size grade silicon carbide powder: the third particle size grade silicon carbide powder = 8:6:5, wherein the particle size of the first particle size grade silicon carbide powder can be set to 20μm~30μm, and the second particle size grade silicon carbide powder can be set to 100μm~200μm. The particle size of the first particle size grade silicon carbide powder is 7μm~20μm, the particle size of the third particle size grade silicon carbide powder is 5μm~15μm, and the first particle size grade silicon carbide powder can also be set to account for 46%~54% of the total mass of the mixed silicon carbide powder, the second particle size grade silicon carbide powder accounts for 16%~20% of the total mass of the mixed silicon carbide powder, and the third particle size grade silicon carbide powder accounts for 26%~38% of the total mass of the mixed silicon carbide powder.
[0075] In some embodiments of the present invention, during the ball milling mixing process, the first raw material: grinding ball: deionized water = 1.0: (1.2-1.5): (1.0-1.2); the grinding ball is a silicon carbide grinding ball.
[0076] In practical applications, 46.0-84.0wt.% SiC, 10.0-15.0wt.% Al, 2.0-28.0wt.% lubricating medium hexagonal BN, 2.0-5.0wt.% Si3N4 and 2.0-6.0wt.% sintering aid can be ball-milled and mixed in deionized water with WC ceramic balls (silicon carbide grinding balls) for 3-5 hours, and the mixed ingredients (i.e., the first raw material) of the ball-milling mixing treatment: grinding balls: deionized water = 1.0: (1.2-1.5): (1.0-1.2), and after drying, a uniformly mixed prefabricated mixture is obtained for subsequent steps.
[0077] Step 102, using the prefabricated mixture, adhesive, surfactant and lubricant as second raw materials, and stirring and mixing the second raw materials to obtain a uniformly mixed prefabricated material;
[0078] In a specific implementation, 81.0-94.0 wt.% of the prefabricated mixture obtained in step 101, 5.0-15.0 wt.% of an adhesive, 1.0-3.0 wt.% of a surfactant and less than 1.0 wt.% of a lubricant may be stirred and mixed to obtain a uniformly mixed prefabricated material. Among them, the adhesive can be a polyvinyl alcohol (PVA) solution with a concentration of 7 to 10 wt.%. PVA has strong adhesion and can enhance the surface tension of the prefabricated mixed particles, which is beneficial to molding and can ensure the body strength of the prefabricated green blanks formed by pressing. Moreover, PVA can have a relatively uniform volatilization rate within the range of 200° C. to 400° C., that is, it slowly volatilizes within the range of 200° C. to 400° C., and the volatilization amount is not much different, which is beneficial to prevent the subsequent sintering and forming of the multiphase silicon carbide ceramic blank from cracking; the surfactant is one or more of polyacrylate, hydroxymethyl cellulose, sodium hydroxymethyl cellulose and lignin sulfonate. The surfactant can better wet and adsorb on the surface of the prefabricated mixed particles, and enhance the surface tension of these particles, further enhance the body strength of the prefabricated green blanks formed by pressing, and is beneficial to molding; the lubricant can be one or more of oleic acid, zinc stearate, magnesium stearate and paraffin. The lubricant can reduce the friction between the particles of the prefabricated mixed material, thereby improving the molding density and strength of the prefabricated green blanks formed by subsequent pressing. Moreover, the synergistic effect of the adhesive, surfactant and lubricant is more effective in reducing the friction between the particles of the prefabricated mixture, and is more effective in improving the density and strength of the prefabricated green material subsequently pressed and formed. This can also improve the density of the subsequent sintered multiphase silicon carbide ceramics, thereby obtaining a multiphase silicon carbide ceramic material with good strength and impact toughness.
[0079] In some embodiments of the present invention, the prefabricated mixture accounts for 81% to 94% of the total mass of the second raw material, the adhesive accounts for 5% to 15% of the total mass of the second raw material, the surfactant accounts for 1% to 3% of the total mass of the second raw material, and the lubricant accounts for 0% to 1% of the total mass of the second raw material.
[0080] In practical applications, 81.0-94.0 wt.% of the prefabricated mixture obtained in step 101, 5.0-15.0 wt.% of an adhesive, 1.0-3.0 wt.% of a surfactant and less than 1.0 wt.% of a lubricant may be stirred and mixed to obtain a uniformly mixed prefabricated material.
[0081] In some embodiments of the present invention, the adhesive is a polyvinyl alcohol solution, the surfactant is one or more of polyacrylate, hydroxymethyl cellulose, sodium hydroxymethyl cellulose and lignin sulfonate, and the lubricant is one or more of oleic acid, zinc stearate, magnesium stearate and paraffin.
[0082] In practical applications, the adhesive can be a polyvinyl alcohol (PVA) solution with a concentration of 7 to 10 wt.%. PVA has strong adhesion and can enhance the surface tension of the prefabricated mixed particles, which is beneficial to molding and can ensure the body strength of the prefabricated green blanks formed by pressing. Moreover, PVA can have a relatively uniform volatilization rate within the range of 200° C. to 400° C., that is, it slowly volatilizes within the range of 200° C. to 400° C., and the volatilization amount is not much different, which is beneficial to prevent the subsequent sintering and forming of the multiphase silicon carbide ceramic blank from cracking; the surfactant is one or more of polyacrylate, hydroxymethyl cellulose, sodium hydroxymethyl cellulose and lignin sulfonate. The surfactant can better wet and adsorb on the surface of the prefabricated mixed particles, and enhance the surface tension of these particles, further enhance the body strength of the prefabricated green blanks formed by pressing, and is beneficial to molding; the lubricant can be one or more of oleic acid, zinc stearate, magnesium stearate and paraffin. The lubricant can reduce the friction between the particles of the prefabricated mixed material, thereby improving the molding density and strength of the prefabricated green blanks formed by subsequent pressing. Moreover, the synergistic effect of the adhesive, surfactant and lubricant is more effective in reducing the friction between the particles of the prefabricated mixture, and is more effective in improving the density and strength of the prefabricated green material subsequently pressed and formed. This can also improve the density of the subsequent sintered multiphase silicon carbide ceramics, thereby obtaining a multiphase silicon carbide ceramic material with good strength and impact toughness.
[0083] Step 103, performing a compression molding process on the prefabricated material to obtain a prefabricated green material;
[0084] In practical applications, the prefabricated material obtained in step 102 can be subjected to one of the compression molding processes of compression molding and / or cold isostatic pressing. The molding pressure can be 60MPa to 120MPa, and the holding time can be 5min to 10min to obtain a prefabricated green material, thereby improving the body density of the prefabricated green material, that is, overcoming the resistance between the powder materials of the prefabricated mixture and the friction between the particles and the mold wall. After holding the pressure, the porosity can be further reduced, thereby improving the density of the subsequent sintered multiphase silicon carbide ceramics.
[0085] In some embodiments of the present invention, the molding pressure of the press molding process is 60MPa to 120MPa, and the holding time is 5min to 10min; the press molding process of the prefabricated material includes:
[0086] The prefabricated material is subjected to compression molding and / or cold isostatic pressing to obtain the prefabricated green material.
[0087] In practical applications, the prefabricated material obtained in step 102 can be subjected to one of the compression molding processes of compression molding and / or cold isostatic pressing. The molding pressure can be 60MPa to 120MPa, and the holding time can be 5min to 10min to obtain a prefabricated green material, thereby improving the body density of the prefabricated green material, that is, overcoming the resistance between the powder materials of the prefabricated mixture and the friction between the particles and the mold wall. After holding the pressure, the porosity can be further reduced, thereby improving the density of the subsequent sintered multiphase silicon carbide ceramics.
[0088] Step 104, heating and debinding the prefabricated green material to obtain a green billet;
[0089] In a specific implementation, the prefabricated blank obtained in step 103 can be heated in a conventional furnace for debinding treatment to obtain a green blank. The temperature can be 200°C to 400°C, and the insulation time can be 0.5h to 3.0h. That is, after heating and insulation, the adhesive, surfactant and lubricant contained in the prefabricated green blank are discharged to avoid the adhesive, surfactant and lubricant remaining in the green blank.
[0090] In some embodiments of the present invention, the temperature of the heating debinding treatment is 200° C. to 400° C., and the insulation time is 0.5 h to 3.0 h.
[0091] In practical applications, the prefabricated blank obtained in step 103 can be heated in a conventional furnace for debinding treatment to obtain a green blank. The temperature can be 200°C to 400°C, and the insulation time can be 0.5h to 3.0h. That is, after heating and insulation, the adhesive, surfactant and lubricant contained in the prefabricated green blank are discharged to avoid the adhesive, surfactant and lubricant remaining in the green blank.
[0092] Step 105, sintering the green body to obtain a composite silicon carbide ceramic blank;
[0093] In a specific implementation, the green body obtained in step 104 can be subjected to a sintering treatment. Specifically, the green body can be subjected to a three-stage sintering treatment, namely, vacuum sintering, atmosphere normal pressure sintering, and atmosphere hot pressing sintering in sequence, to obtain a highly densified composite silicon carbide ceramic blank. Among them, the vacuum sintering treatment in the three-stage sintering treatment can be: before the temperature rises to 1600°C to 1800°C, the gas pressure is controlled to be less than 100Pa, and vacuum sintering is performed; the atmosphere normal pressure sintering treatment in the three-stage sintering treatment can be: after the temperature reaches 1600°C to 1800°C and 0.1MPa of nitrogen is introduced, the temperature can be then raised to 2000°C to 2300°C, kept warm for 0.5h to 1.5h, and atmosphere normal pressure sintering is performed; the atmosphere hot pressing sintering treatment in the three-stage sintering treatment can be: after the atmosphere normal pressure sintering treatment, nitrogen is continued to be introduced, and then the gas pressure is raised to 0.5MPa to 1.0MPa, and then kept warm for 1h to 2h, and atmosphere hot pressing sintering is performed. The density of the composite silicon carbide ceramic blank after three-stage sintering is high. The vacuum environment and protective atmosphere can also prevent Al, AlN, and BN from being oxidized to form oxides. The role played by these phases in the composite silicon carbide will not be lost, especially the lubricating effect of hexagonal BN can be maintained.
[0094] In some embodiments of the present invention, the sintering of the green compact comprises:
[0095] The green body is subjected to vacuum sintering treatment, atmosphere normal pressure sintering treatment and atmosphere hot pressing sintering treatment in sequence to obtain the composite silicon carbide ceramic blank.
[0096] In practical applications, the green body obtained in step 104 can be sintered. Specifically, the green body can be subjected to vacuum sintering, atmospheric pressure sintering and atmosphere hot pressing sintering in sequence, i.e., three-stage sintering, to obtain a highly densified multiphase silicon carbide ceramic blank.
[0097] In some embodiments of the present invention, the green body is subjected to vacuum sintering, atmospheric pressure sintering and atmosphere hot pressing sintering in sequence, including:
[0098] Acquiring sintering temperature information in a sintering environment, and controlling the sintering gas pressure in the sintering environment to be less than 100 Pa before the sintering temperature rises to 1600° C. to 1800° C., so as to perform the vacuum sintering treatment on the green body;
[0099] When the sintering temperature rises to 1600° C. to 1800° C., 0.1 MPa of nitrogen is introduced into the sintering environment, and then the sintering temperature is controlled to rise to 2000° C. to 2300° C. and kept at this temperature for 0.5 h to 1.5 h, so as to perform the atmosphere normal pressure sintering treatment on the green body;
[0100] After the atmospheric pressure sintering treatment is completed, the nitrogen gas is continuously introduced into the sintering environment, and the sintering gas pressure is increased to 0.5 MPa to 1.0 MPa, and then the temperature is maintained for 1 h to 2 h to perform the atmospheric hot pressing sintering treatment on the green body.
[0101] In practical applications, the vacuum sintering treatment in the three-stage sintering treatment can be: before the temperature rises to 1600℃~1800℃, the gas pressure is controlled to be less than 100Pa, and vacuum sintering is performed; the atmosphere normal pressure sintering treatment in the three-stage sintering treatment can be: after the temperature reaches 1600℃~1800℃ and 0.1MPa of nitrogen is introduced, the temperature can be then raised to 2000℃~2300℃, kept warm for 0.5h~1.5h, and atmosphere normal pressure sintering is performed; the atmosphere hot pressing sintering treatment in the three-stage sintering treatment can be: after the atmosphere normal pressure sintering treatment, nitrogen is continued to be introduced, and then the gas pressure is increased to 0.5MPa~1.0MPa, and then kept warm for 1h~2h, and atmosphere hot pressing sintering is performed. The density of the composite silicon carbide ceramic blank after three-stage sintering is high. The vacuum environment and protective atmosphere can also prevent Al, AlN, and BN from being oxidized to form oxides. The role played by these phases in the composite silicon carbide will not be lost, especially the lubricating effect of hexagonal BN can be maintained.
[0102] Step 106: machining the composite silicon carbide ceramic blank to obtain the composite silicon carbide ceramic.
[0103] In a specific implementation, the blank obtained in step 105 can be machined to obtain a composite silicon carbide ceramic component, thereby completing the preparation process of the composite silicon carbide ceramic.
[0104] Further, such as Figure 2 The figure shows the overall flow chart of the preparation method of the multiphase silicon carbide ceramic provided by the present invention, which comprises Figure 2 It can be seen from the content that the overall execution process of the present invention can be summarized as follows:
[0105] (1) 46.0-84.0 wt.% of SiC, 10.0-15.0 wt.% of Al, 2.0-28.0 wt.% of hexagonal BN as a lubricating medium, 2.0-5.0 wt.% of Si3N4 and 2.0-6.0 wt.% of a sintering aid are ball-milled and mixed in deionized water for 3-5 hours, and dried to obtain a uniformly mixed pre-mixed material;
[0106] (2) Calculated by mass percentage: 81.0-94.0 wt.% of the prefabricated mixture obtained in step (1), 5.0-15.0 wt.% of an adhesive, 1.0-3.0 wt.% of a surfactant, and less than 1.0 wt.% of a lubricant are stirred and mixed to obtain a uniformly mixed prefabricated material;
[0107] (3) subjecting the prefabricated material obtained in step (2) to a compression molding process of compression molding and / or cold isostatic pressing, wherein the molding pressure is 60 MPa to 120 MPa and the holding time is 5 min to 10 min, to obtain a prefabricated green material;
[0108] (4) heating the prefabricated green material obtained in step (3) in a conventional furnace to remove binder to obtain a green body, the temperature being 200° C. to 400° C. and the holding time being 0.5 h to 3.0 h;
[0109] (5) The green body obtained in step (4) is subjected to a sintering treatment, and the green body is subjected to a three-stage sintering treatment of vacuum sintering, atmosphere normal pressure sintering and atmosphere hot pressing sintering in sequence, so as to obtain a highly densified multiphase silicon carbide ceramic blank.
[0110] (6) Machining the blank obtained in step (5) to obtain a complex silicon carbide ceramic component.
[0111] In one example, a prefabricated material obtained by uniformly mixing 87.5wt.% of a prefabricated mixture (SiC, Al, hexagonal BN, Si3N4 and sintering aid Y2O3 in different weight percentages), 10.0wt.% of a binder, 2.0% of a surfactant and 0.5wt.% of a lubricant is taken as an example. The prefabricated material can be molded at 90.0MPa and maintained at a pressure of 7.5min to obtain a prefabricated green material. Then, the obtained prefabricated green material is subjected to 300 After 1.75 hours of debinding at ℃, a green body is obtained. Finally, the green body is heated to 1800℃ in a vacuum environment with a pressure of 100Pa for vacuum sintering. Then, 0.1MPa of nitrogen is introduced, and the temperature is raised to 2300℃ and kept warm for 1.5 hours for atmosphere normal pressure sintering. Finally, nitrogen is continued to be introduced to increase the pressure to 1.0MPa and then kept warm for 2 hours for atmosphere hot pressing sintering. The performance comparison example of the composite silicon carbide ceramic material obtained after the three-stage sintering treatment is shown in Table 1 below:
[0112] Table 1: Comparison of properties of composite silicon carbide ceramic materials in Example 1
[0113]
[0114] In one example, a prefabricated material obtained by uniformly mixing 87.5wt.% of a prefabricated mixture (65.0wt.% of SiC, 12.5wt.% of Al, 15.0wt.% of hexagonal BN, 3.5wt.% of Si3N4 and sintering aid BeO of different mass percentages), 10.0wt.% of a binder, 2.0% of a surfactant and 0.5wt.% of a lubricant is taken as an example. The prefabricated material can be molded at 90.0MPa and maintained at a pressure of 7.5min to obtain a prefabricated green material, and then The obtained prefabricated green body was subjected to debinding at 300°C for 1.75h to obtain a green body, and finally the green body was heated to 1800°C in a vacuum environment with a pressure of 100Pa for vacuum sintering, and then 0.1MPa nitrogen was introduced, and the temperature was raised to 2300°C and kept warm for 1.5h for atmosphere normal pressure sintering, and finally nitrogen was continued to be introduced, so that the pressure was raised to 1.0MPa and kept warm for 2h for atmosphere hot pressing sintering. The performance comparison example of the composite silicon carbide ceramic material obtained after the three-stage sintering treatment is shown in Table 2 below:
[0115] Table 2: Comparison of properties of composite silicon carbide ceramic materials in Example 2
[0116]
[0117] In one example, a prefabricated material obtained by uniformly mixing 87.5wt.% of a prefabricated mixture (65.0wt.% of SiC, 12.5wt.% of Al, 15.0wt.% of hexagonal BN, 3.5wt.% of Si3N4 and sintering aid B4C of different mass percentages), 10.0wt.% of a binder, 2.0% of a surfactant and 0.5wt.% of a lubricant is taken as an example. The prefabricated material can be molded at 90.0MPa and maintained at a pressure of 7.5min to obtain a prefabricated green material, and then The obtained prefabricated green body was subjected to debinding at 300°C for 1.75h to obtain a green body, and finally the green body was heated to 1800°C in a vacuum environment with a pressure of 100Pa for vacuum sintering, and then 0.1MPa nitrogen was introduced, and the temperature was raised to 2300°C and kept warm for 1.5h for atmosphere normal pressure sintering, and finally nitrogen was continued to be introduced, so that the pressure was raised to 1.0MPa and kept warm for 2h for atmosphere hot pressing sintering. The performance comparison example of the composite silicon carbide ceramic material obtained after the three-stage sintering treatment is shown in Table 3 below:
[0118] Table 3: Comparison of properties of composite silicon carbide ceramic materials in Example 3
[0119]
[0120]
[0121] In one example, a prefabricated mixture obtained by mixing 65.0wt.% SiC, 12.5wt.% Al, 15.0wt.% hexagonal BN, 3.5wt.% Si3N4 and 4.0wt.% sintering aid Y2O3 is taken as an example. After adding different amounts of adhesive, surfactant and lubricant to the prefabricated mixture to mix evenly and press to form, the performance comparison example of the obtained prefabricated green blank is shown in Table 4 below:
[0122] Table 4: Comparative table of properties of prefabricated green materials in Example 4
[0123]
[0124] In one example, a prefabricated material obtained by uniformly mixing 87.5wt.% of a prefabricated mixture (65.0wt.% of SiC, 12.5wt.% of Al, 15.0wt.% of hexagonal BN, 3.5wt.% of Si3N4 and 4.0wt.% of a sintering aid Y2O3), 10.0wt.% of an adhesive, 2.0% of a surfactant and 0.5wt.% of a lubricant is taken as an example. The prefabricated material can be molded at 90.0MPa and maintained at a pressure of 7.5min. The obtained prefabricated green body is then subjected to a debinding treatment at different temperatures and times. The performance comparison example of the obtained green body is shown in Table 5 below:
[0125] Table 5: Comparative table of green body properties of Example 5
[0126]
[0127] In one example, a prefabricated material obtained by uniformly mixing 87.5wt.% of a prefabricated mixture (65.0wt.% of SiC, 12.5wt.% of Al, 15.0% of hexagonal BN, 3.5wt.% of Si3N4 and 4.0wt.% of a sintering aid Y2O3), 10.0wt.% of an adhesive, 2.0% of a surfactant and 0.5wt.% of a lubricant is taken as an example, the prefabricated material can be molded at 90.0MPa, and the prefabricated green material can be obtained after holding the pressure for 7.5min. The prefabricated green material is subjected to 300°C debinding for 1.75h to obtain a green body, and finally the green body is subjected to a three-stage sintering treatment at different temperatures and times. The material properties of the obtained multiphase silicon carbide blank are compared in the following Table 6:
[0128] Table 6: Comparison of properties of multiphase silicon carbide blanks in Example 6
[0129]
[0130]
[0131] On the basis of the above contents, the technical effects achieved by the present invention will be further described below in combination with a piston compressor of a multiphase silicon carbide ceramic prepared by the above preparation method of the present invention:
[0132] In some embodiments of the present invention, Figure 3 , Figure 4 and Figure 5 The figures are a cross-sectional view of the whole machine, a three-dimensional view of the core assembly and a three-dimensional view of the pump assembly of the piston compressor (hereinafter referred to as the piston compressor or compressor) using the multiphase silicon carbide ceramic of the present invention. Figure 3 , Figure 4 and Figure 5 It can be seen from the content that the piston compressor is mainly composed of a housing assembly 100, a motor assembly 220 and a pump body assembly. The pump body assembly is mainly composed of a cylinder seat 210, a crankshaft assembly 230, a connecting rod 240, a piston assembly 250, a valve assembly 260, a muffler assembly 270 and an end cover 280. The crankshaft assembly 230 is driven to rotate by the motor assembly 220, thereby driving the piston assembly 250 connected to the connecting rod 240 to perform reciprocating linear motion.
[0133] Further, such as Figure 6 , Figure 7 , Figure 8 , Fig. 9 and Fig.10 The three-dimensional diagrams of the piston assembly, crankshaft assembly and connecting rod assembly, crankshaft 3D diagram, connecting rod 3D diagram and cross-sectional diagram, piston 3D diagram and piston pin 3D diagram of the piston compressor are shown respectively. Figure 6 , Figure 7 , Figure 8 , Fig. 9 and Fig.10 It can be seen that the crankshaft assembly 230 is mainly composed of a crankshaft 231 and a counterweight 232, and a main oil passage, a branch oil passage and a spiral oil passage are provided on the crankshaft 231. The branch oil passage is mainly composed of a first branch oil passage 231b, a second branch oil passage 231c and a third branch oil passage 231e, and the spiral oil passage is mainly composed of a first spiral oil passage 231d and a second spiral oil passage 231f. A straight oil passage 243 is provided in the center of the rod portion 241 between the main shaft hole 242 and the secondary shaft hole 243 of the connecting rod 240, which is connected to the main shaft hole 242 and the secondary shaft hole 243.
[0134] Furthermore, the first branch oil passage 231b is connected to the main oil passage 231a, and the second branch oil passage 231c is connected to the first branch oil passage 231b. Lubricating oil is pumped out from the oil outlet of the first branch oil passage 231b, thereby forming an oil film between the piston 251 and the cylinder of the cylinder seat 210 and between the piston pin 252 and the connecting rod 240. The oil film provides sealing and lubrication for these friction matching parts that cooperate with each other, and the lubricating oil can also cool the cylinder seat 231, the piston 251 and the piston pin 252; the first spiral oil passage 231d is connected to the main oil passage 231a, thereby forming an oil film between the crankshaft 231 and the sleeve of the cylinder seat 210 to provide lubrication; the third branch oil passage 231e is connected to the first spiral oil passage 231d, The lubricating oil is pumped out from the oil outlet of the third oil channel 231e, and then an oil film is formed between the piston 251 and the cylinder of the cylinder seat 210 and between the piston pin 252 and the connecting rod 240, thereby providing sealing and lubrication for these friction matching parts that cooperate with each other, and the lubricating oil can also increase the cooling effect on the cylinder seat 231, the piston 251 and the piston pin 252; the second spiral oil channel 231f is connected to the third oil channel 231e, and the second spiral oil channel 231f not only provides oil film lubrication and cooling for the main shaft hole 242 of the connecting rod 240, but also lubricates and cools the secondary shaft hole 243 and the piston pin 252 of the connecting rod 240 that cooperate with each other through the straight oil channel 244 of the connecting rod 240 connected to the second spiral oil channel 231f.
[0135] Among them, the lubricating oil is pumped from the bottom of the compressor chamber shell to each main oil channel, branch oil channel and spiral oil channel by the pumping structure of the crankshaft 231. For example, the lubricating oil is pumped from the end of the second branch oil channel 231c, the end of the third branch oil channel 231e and the end of the second spiral oil channel 231f to the upper end of the core assembly 200 near the upper cover of the casing to provide lubrication and cooling for the pump body assembly at the upper end of the core assembly 200. The specific flow direction of the lubricating oil is as follows: Figure 3 shown.
[0136] Further, such as Fig.11 As shown in the figure, the piston compressor for refrigerators will generate lateral force and residual reciprocating inertia force during operation. These two forces are the main excitation sources that cause the vibration and noise of the compressor to increase. Moreover, these two forces will increase with the increase of the weight of the piston 251, the piston pin 252, the connecting rod 240, the eccentric part of the crankshaft 231 and the counterweight block 232, and the vibration and noise will increase. After replacing one or more of the components of the piston 251, the piston pin 252, the connecting rod 240 and the crankshaft 231 whose substrates are iron-based materials with the multiphase silicon carbide ceramic material of the present invention, the lateral force and the residual reciprocating inertia force are greatly reduced, and the noise of the compressor is greatly improved, especially the improvement effect on the noise generated when the compressor is running at high frequency is the most obvious, and the high-frequency noise is reduced by about 6dB. The specific noise test results are shown in FIG. Fig.12 shown.
[0137] Furthermore, from the foregoing content, it can be seen that the multiphase silicon carbide ceramic material of the present invention is composed of 46.0-84.0wt.% SiC, 10.0-15.0wt.% Al, 2.0-28.0wt.% lubricating medium hexagonal BN, 2.0-5.0wt.% Si3N4 and 2.0-6.0wt.% sintering aid raw materials, and the sintering aid is any one or more of B4C, Y2O3 and BeO.
[0138] Among them, Al, which is easily soluble in SiC, forms a substitutional solid solution with SiC at high temperature, thereby promoting the sintering of the multiphase silicon carbide ceramic to be denser; and part of Al forms an AlN ceramic phase with a thermal conductivity of 50 to 75 W / (mm°C) when sintered in a nitrogen atmosphere. The AlN is also a sintering aid for SiC ceramics, further making the sintered multiphase silicon carbide ceramic material denser; hexagonal BN has self-lubricating properties, and its lubricating properties are better than other solid lubricants (such as molybdenum disulfide and graphite). It can also maintain good self-lubricating properties at high temperatures. After adding the lubricating medium hexagonal BN, it can not only improve the processing performance of the multiphase silicon carbide ceramic, enhance its material toughness, and is not prone to collapse and fragmentation during processing, but also The invention can enhance the self-lubricating property of the composite silicon carbide ceramics; Si3N4 can form a liquid phase during high temperature sintering and infiltrate into the pores of the prefabricated green body formed by pressing, thereby improving the sintering property and increasing the density of the composite silicon carbide ceramics; after adding any one or more sintering aids of B4C, Y2O3 and BeO, the dispersion of SiC ceramic phase, AlN ceramic phase, BN ceramic phase and Si3N4 ceramic phase in the composite silicon carbide ceramics can be further reduced, that is, these ceramic phases are distributed more evenly, thereby increasing the strength of the green body and further improving the density of the green body; since the sintering molding temperature of SiC is 2000℃~2300℃, in order to prevent these sintering aids from melting and decomposing at high temperature, thereby causing AlN, Si3N4 and Al to be decomposed, O 2- Therefore, the melting point of the sintering aid needs to be controlled above 2300°C.
[0139] The above Al, AlN formed by the reaction, hexagonal BN, Si3N4 and sintering aids play a synergistic improvement role on the multiphase silicon carbide ceramics, so that the multiphase silicon carbide ceramic material after sintering has high density, good impact toughness, high hardness, strong wear resistance, high thermal conductivity, good friction reduction and self-lubrication, and a higher thermal expansion coefficient than the existing silicon carbide ceramics. It is easy to process and reduces the wear of PCD tools and diamond grinding wheels.
[0140] Among them, the density of multiphase silicon carbide ceramics is 2.7-3.0 g / cm 3, its density is only 1 / 3 of the existing iron-based material, so that the lateral force and residual reciprocating inertia force generated by the piston compressor during operation are greatly reduced, and the compressor noise caused by these two unbalanced forces is greatly improved, especially the improvement effect on the noise generated by the high-frequency operation of the compressor is the most obvious. The comparison of the two unbalanced forces and noise between the conventional solution and the solution of the present invention is as follows: Fig.11 and Fig.12 shown.
[0141] Since Al (22.5~22.3×10 -6 / ℃), and partially reacts with nitrogen at high temperature to form AlN with a relatively high linear expansion coefficient (5.0~6.0×10 -6 / ℃), so that the thermal expansion coefficient of the composite silicon carbide ceramic can reach (6.0~7.3)×10 -6 / ℃, that is, its thermal expansion coefficient is higher than that of existing silicon carbide ceramic materials. After the multiphase silicon carbide ceramic material is used as a base material for one or more of the piston 251, piston pin 252, connecting rod and crankshaft 231 of the piston compressor, these multiphase silicon carbide ceramic parts have a thermal expansion coefficient of (10.0~11.0)×10 -6 / ℃ cast iron material, the fitting clearance between these complex phase silicon carbide components and cast iron components under high-frequency conditions is much smaller than that of existing silicon carbide ceramics, that is, the leakage under high-frequency conditions is reduced and the cooling capacity is improved.
[0142] At the same time, since the thermal conductivity of the raw materials SiC (120W / (mmK)), Al (100W / (mmK)), AlN (70W / (mmK)) and BN (50W / (mmK)) is higher than that of the existing iron-based materials (50W / (mmK)), the thermal conductivity of the high-density multiphase silicon carbide ceramic can reach more than 80W / (mmK), that is, the thermal conductivity of the multiphase silicon carbide ceramic material of the present invention is at least 2 times higher than that of the existing iron-based materials. After the material is used as the base material for one or more of the piston 251, piston pin 252, connecting rod 240 and crankshaft 231 of the piston compressor, the heat generated by the compressed refrigerant gas can be transferred to the piston 251, piston pin 252, connecting rod 240 and crankshaft 231 in time, and the transferred heat is then carried away by the lubricating oil flowing through the inside or surface of these components. In this way, the low-temperature refrigerant gas entering the compression chamber again will not be heated and expanded, and the amount of low-temperature refrigerant gas inhaled will not decrease, thereby increasing the cooling capacity of the compressor.
[0143] The low leakage between the pump body parts and the unchanged amount of refrigerant gas inhaled by the compressor under high-frequency working conditions improve the high-frequency refrigeration capacity of the compressor. The refrigeration capacity comparison between the piston compressor in the conventional scheme and the piston compressor in the scheme of the present invention is as follows: Fig.13 As shown, it can be seen that the high-frequency performance of the piston compressor has also been greatly improved.
[0144] Furthermore, the raw materials of the multiphase silicon carbide ceramic are added with a lubricating hexagonal BN phase. The hexagonal BN phase with good self-lubricating properties not only improves the processing performance of the existing hard and brittle silicon carbide ceramic materials, making the multiphase silicon carbide ceramic materials easier to process, thereby reducing the wear of PCD tools and diamond grinding wheels, but also improves the self-lubricating properties of the multiphase silicon carbide ceramics, and reduces the friction coefficient when it is matched with iron-based parts for grinding. The friction coefficient comparison between the conventional scheme and the scheme of the present invention is as follows: Fig.14 As shown in the figure, the friction coefficient of the scheme of the present invention is lower than that of the conventional scheme, and the friction resistance of the scheme of the present invention is smaller, so that the friction coefficient curve of the scheme of the present invention is smoother and the friction power consumption is lower; after the multiphase silicon carbide ceramic material is used as a base material for one or more of the piston 251, the piston pin 252, the connecting rod 240 and the crankshaft 231 of the piston compressor, the power consumption of the compressor of the conventional scheme and the scheme of the present invention is compared. Fig.15 As shown, it can be seen that the friction power consumption between the internal pump body parts of the compressor is reduced, and the compressor performance is further improved.
[0145] In summary, through the preparation method of the multiphase silicon carbide ceramic provided by the present invention, the density of the prepared multiphase silicon carbide ceramic material is only 2 / 5 times that of the existing conventional iron-based powder metallurgy material. After the new multiphase silicon carbide ceramic material is used as the substrate of unbalanced deflection structures such as pistons, piston pins, connecting rods and crankshafts, the unbalanced inertial force generated during the operation of the compressor is greatly reduced; the hardness of the new multiphase silicon carbide ceramic material is second only to diamond, with high hardness and good wear resistance, and can meet the requirements of long-term reliable operation of the compressor under high-frequency and high-speed conditions; the thermal conductivity of the new multiphase silicon carbide ceramic material is more than twice that of iron-based powder metallurgy, and the heat generated in the compressor cavity can be transferred to the refrigeration oil outside the cylinder and taken away by the refrigeration oil; a lubricating phase is added to the new multiphase silicon carbide ceramic material, which can play a self-lubricating effect of friction reduction and lubrication in the process of grinding with other components; after the lubricating phase is added to the new multiphase silicon carbide ceramic material, it is easier to process and shape, reducing the loss of PCD tools and diamond grinding wheels.
[0146] It should be noted that, for the sake of simplicity, the method embodiments are described as a series of action combinations, but those skilled in the art should be aware that the embodiments of the present invention are not limited by the order of the actions described, because according to the embodiments of the present invention, certain steps can be performed in other orders or simultaneously. Secondly, those skilled in the art should also be aware that the embodiments described in the specification are all preferred embodiments, and the actions involved are not necessarily required by the embodiments of the present invention.
[0147] Some embodiments of the present invention further provide a multiphase silicon carbide ceramic, wherein the multiphase silicon carbide ceramic is prepared by the method for preparing the multiphase silicon carbide ceramic as described above.
[0148] Some embodiments of the present invention further provide a compressor, comprising the multiphase silicon carbide ceramic as described above.
[0149] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0150] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the embodiments of the present invention.
[0151] Finally, it should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or terminal device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or terminal device. In the absence of further restrictions, the elements defined by the sentence "including one..." do not exclude the existence of other identical elements in the process, method, article or terminal device including the above elements.
[0152] The above is a detailed introduction to a preparation method of a composite silicon carbide ceramic and a composite silicon carbide ceramic. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for a person skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A method for preparing a multiphase silicon carbide ceramic, characterized in that: The method comprises: Silicon carbide, aluminum, hexagonal boron nitride, silicon nitride and a sintering aid are used as first raw materials, and the first raw materials are subjected to ball milling and mixing treatment in deionized water to obtain a uniformly mixed prefabricated mixture; The prefabricated mixed material, adhesive, surfactant and lubricant are used as the second raw material, and the second raw material is stirred and mixed to obtain a uniformly mixed prefabricated material; The prefabricated material is subjected to a compression molding process to obtain a prefabricated green material; The prefabricated green material is subjected to a heating and debinding treatment to obtain a green billet; Sintering the green body to obtain a composite silicon carbide ceramic blank; The composite silicon carbide ceramic blank is machined to obtain the composite silicon carbide ceramic.
2. The method according to claim 1, characterized in that The silicon carbide accounts for 46% to 84% of the total mass of the first raw material, the aluminum accounts for 10% to 15% of the total mass of the first raw material, the hexagonal boron nitride accounts for 2% to 28% of the total mass of the first raw material, the silicon nitride accounts for 2% to 5% of the total mass of the first raw material, the sintering aid accounts for 2% to 6% of the total mass of the first raw material, and the processing time of the ball milling mixing treatment is 3h to 5h.
3. The method according to claim 1, characterized in that The prefabricated mixture accounts for 81% to 94% of the total mass of the second raw material, the adhesive accounts for 5% to 15% of the total mass of the second raw material, the surfactant accounts for 1% to 3% of the total mass of the second raw material, and the lubricant accounts for 0% to 1% of the total mass of the second raw material.
4. The method according to claim 1, characterized in that: The molding pressure of the compression molding process is 60MPa to 120MPa, and the holding time is 5min to 10min; the compression molding process of the prefabricated material includes: The prefabricated material is subjected to compression molding and / or cold isostatic pressing to obtain the prefabricated green material.
5. The method according to claim 1, characterized in that The temperature of the heating debinding treatment is 200° C. to 400° C., and the insulation time is 0.5 h to 3.0 h.
6. The method according to claim 1, characterized in that The step of sintering the green compact comprises: The green body is subjected to vacuum sintering treatment, atmosphere normal pressure sintering treatment and atmosphere hot pressing sintering treatment in sequence to obtain the composite silicon carbide ceramic blank.
7. The method according to claim 6, characterized in that The green body is subjected to vacuum sintering treatment, atmospheric pressure sintering treatment and atmosphere hot pressing sintering treatment in sequence, including: Acquiring sintering temperature information in a sintering environment, and controlling the sintering gas pressure in the sintering environment to be less than 100 Pa before the sintering temperature rises to 1600° C. to 1800° C., so as to perform the vacuum sintering treatment on the green body; When the sintering temperature rises to 1600° C. to 1800° C., 0.1 MPa of nitrogen is introduced into the sintering environment, and then the sintering temperature is controlled to rise to 2000° C. to 2300° C. and kept at this temperature for 0.5 h to 1.5 h, so as to perform the atmosphere normal pressure sintering treatment on the green body; After the atmospheric pressure sintering treatment is completed, the nitrogen gas is continuously introduced into the sintering environment, and the sintering gas pressure is increased to 0.5 MPa to 1.0 MPa, and then the temperature is maintained for 1 h to 2 h to perform the atmospheric hot pressing sintering treatment on the green body.
8. The method according to claim 1, characterized in that The melting point of the sintering aid is higher than 2300° C. The sintering aid is one or more of boron carbide, yttrium trioxide and beryllium oxide.
9. The method according to claim 1, characterized in that: The silicon carbide is a mixed silicon carbide powder containing three particle size grades, wherein the first particle size grade silicon carbide powder: the second particle size grade silicon carbide powder: the third particle size grade silicon carbide powder = 8:6:5; The first particle size grade silicon carbide powder accounts for 46% to 54% of the total mass of the mixed silicon carbide powder, the second particle size grade silicon carbide powder accounts for 16% to 20% of the total mass of the mixed silicon carbide powder, and the third particle size grade silicon carbide powder accounts for 26% to 38% of the total mass of the mixed silicon carbide powder; The particle size of the silicon carbide powder of the first particle size grade is 20 μm to 30 μm, the particle size of the silicon carbide powder of the second particle size grade is 7 μm to 20 μm, and the particle size of the silicon carbide powder of the third particle size grade is 5 μm to 15 μm.
10. The method according to claim 1, characterized in that During the ball milling mixing process, the first raw material: grinding ball: deionized water = 1.0: (1.2-1.5): (1.0-1.2); the grinding ball is a silicon carbide grinding ball.
11. The method according to claim 1, characterized in that: The adhesive is a polyvinyl alcohol solution, the surfactant is one or more of polyacrylate, hydroxymethyl cellulose, sodium hydroxymethyl cellulose and lignin sulfonate, and the lubricant is one or more of oleic acid, zinc stearate, magnesium stearate and paraffin.
12. A multiphase silicon carbide ceramic, characterized in that: The multiphase silicon carbide ceramic is prepared by the method for preparing the multiphase silicon carbide ceramic according to any one of claims 1 to 11.
13. A compressor, characterized in that: The compressor includes the multi-phase silicon carbide ceramic according to claim 12 .
Citation Information
Patent Citations
Silicon carbide-boron nitride ceramics composite material
CN101058507A
Beta-Sialon-Si3N4-SiC composite ceramic material
CN103664179A
Hot pressed sintering method of ceramic products with high density and complex shapes
CN103896601A
Silicon carbide ceramic and low temperature sintering method thereof
CN104030687A
High temperature nitridation sintered metal-nitride combined silicon carbide brick and preparation method thereof
CN105924182A
Cited By
Die surface self-lubricating coating and application thereof
CN120060787A
